Petiole vascular bundles and its taxonomic value in the tribe Dipterocarpeae (Dipterocarpaceae) - Noraini Talip,; Mohamad Ruzi Abdul Rahman,; Ismail Sahid,; Ummu Hani Badron,; Salwa Sahimi,; J. Azi Azeyanty, (Universiti Kebangsaan Malaysia, 2016)
A comprehensive survey and descriptions on the petiole anatomy was undertaken on 16 species belonging to four selected genera (Anisoptera, Cotylelobium, Vatica and Upuna) in the tribe Dipterocarpeae to investigate variations in vascular bundle structure. Methods used in this study were petiole sectioning using a sliding microtome, staining, mounting and observation under light microscope. Findings had shown that all species studied have complex vascular bundle structures, consisting of outer and medullary vascular bundles. Four different types of vascular bundle arrangements were found and described as Types 1, 2, 3 and 4. The vascular bundle types were determined based on the arrangement and system of vascular bundle strands present in the petiole transverse sections. These vascular bundle types were determined and suggested for easy reference. The results showed that vascular bundles can be used for identification of certain species and can definitely be used for classification of different genera. The presence of sclerenchyma cells is useful in differentiating genera. As a conclusion, the petiole vascular bundle anatomical characteristics have taxonomic value, especially in the identification of some species and possibly applicable in the classification of the tribe Dipterocarpeae.